2016
DOI: 10.1038/ncomms13567
|View full text |Cite
|
Sign up to set email alerts
|

IRS4 induces mammary tumorigenesis and confers resistance to HER2-targeted therapy through constitutive PI3K/AKT-pathway hyperactivation

Abstract: In search of oncogenic drivers and mechanisms affecting therapy resistance in breast cancer, we identified Irs4, a poorly studied member of the insulin receptor substrate (IRS) family, as a mammary oncogene by insertional mutagenesis. Whereas normally silent in the postnatal mammary gland, IRS4 is found to be highly expressed in a subset of breast cancers. We show that Irs4 expression in mammary epithelial cells induces constitutive PI3K/AKT pathway hyperactivation, insulin/IGF1-independent cell proliferation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 61 publications
(81 reference statements)
3
69
0
Order By: Relevance
“…1B for a schematic overview). IRS4 -expression could also rapidly be attained in naive HER2+ breast cancer cell lines by culturing the cells for several passages in medium with increasing concentrations of trastuzumab or lapatinib, indicating selection for IRS4 -expressing cells under the pressure of the drugs 5 . Hence, our data suggest that IRS4 can cause both primary resistance to trastuzumab or lapatinib, as well as acquired resistance during treatment, thus likely plays a role in relapse in breast cancer patients.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…1B for a schematic overview). IRS4 -expression could also rapidly be attained in naive HER2+ breast cancer cell lines by culturing the cells for several passages in medium with increasing concentrations of trastuzumab or lapatinib, indicating selection for IRS4 -expressing cells under the pressure of the drugs 5 . Hence, our data suggest that IRS4 can cause both primary resistance to trastuzumab or lapatinib, as well as acquired resistance during treatment, thus likely plays a role in relapse in breast cancer patients.…”
mentioning
confidence: 59%
“…Hence, our data suggest that IRS4 can cause both primary resistance to trastuzumab or lapatinib, as well as acquired resistance during treatment, thus likely plays a role in relapse in breast cancer patients. Importantly, we also showed that treating HER2+ breast cancer cells expressing IRS4 with a HER2-targeting drug in combination with a PI3K-specific inhibitor abrogated IRS4-mediated resistance, even in suboptimal doses 5 . This finding may inspire the field to keep investigating the combination of HER2-targeted drugs with PI3K, AKT and/or mTOR inhibitors, despite the limited success of initial clinical trials.…”
mentioning
confidence: 60%
See 3 more Smart Citations